Les habitats carolingiens de Montours et La Chapelle-Saint-Aubert (Ille-et-Vilaine) - Catteddu, Isabelle (Documents d'archéologie française, 2001)
From 1995 to 1997, four early medieval sites were excavated in the Fougères region as part of archaeological research work carried out prior to the construction of the A84 motarway. As the sites all date from the same period, a comprehensive research plan was implemented from the outset, with special emphasis on paleo-environmental analysis and examination of pottery finds. Examination of the three Carolingian settlement sites, as well as a ford from the same period, reveals an organised, interactive approach to environmental management of the surrounding lands (land division, ditch Systems. tracks, development of a peatcovered valley floor), which were developed and systematically exploited from the 7th to 10th century. The present volume provides a significant contribution to our understanding of early medieval rural settlements in Brittany, an area of study which has hitherto received little attention from archaeologists The research is enhanced by an analysis of bio-archaeological data from the sites, showing the impact of agro-pastoral activities on the landscape and vegetation in nearby areas.